Thresholds for clinically important deterioration versus improvement in COPD health status: results from a randomised controlled trial in pulmonary rehabilitation and an observational study during routine clinical practice. Issue 6 (28th June 2019) - Alma, Harma Johanna; de Jong, Corina; Jelusic, Danijel; Wittmann, Michael; Schuler, Michael; Sanderman, Robbert; Schultz, Konrad; Kocks, Janwillem; van der Molen, Thys
Abstract : Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease. Preventing deterioration of health status is therefore an important therapy goal. (Minimal) Clinically Important Differences ((M)CIDs) are used to interpret changes observed. It remains unclear whether (M)CIDs are similar for both deterioration and improvement in health status. This study investigates and compares these clinical thresholds for three widely-used questionnaires. Design and setting: Data were retrospectively analysed from an inhouse 3-week pulmonary rehabilitation (PR) randomised controlled trial in the German Klinik Bad Reichenhall (study 1), and observational research in Dutch primary and secondary routine clinical practice (RCP) (study 2). Participants: Patients with COPD aged ≥18 years (study 1) and aged ≥40 years (study 2) without respiratory comorbidities were included for analysis. Primary outcomes: The COPD Assessment Test (CAT), Clinical COPD Questionnaire (CCQ) and St George's Respiratory Questionnaire (SGRQ) were completed at baseline and at 3, 6 and 12 months. A Global Rating of Change scale was added at follow-up. Anchor-based and distribution-based methods were used to determine clinically relevant thresholds. Results: In total, 451 patients were included from PR and 207 from RCP. MCIDs for deterioration ranged from 1.30 to 4.21 (CAT), from 0.19 to 0.66 (CCQ), and from 2.75 to 7.53 (SGRQ). MCIDs for improvement ranged from −3.78 to −1.53 (CAT), from −0.50 to −0.19 (CCQ), and from −9.20 to −2.76 (SGRQ). Thresholds for moderate improvement versus deterioration ranged from −5.02 to −3.29 vs 3.89 to 8.14 (CAT), from −0.90 to −0.72 vs 0.42 to 1.23 (CCQ), and from −15.85 to −13.63 vs 7.46 to 9.30 (SGRQ). Conclusions: MCID ranges for improvement and deterioration on the CAT, CCQ and SGRQ were somewhat similar. However, estimates for moderate and large change varied and were inconsistent. Thresholds differed between study settings. Trial registration number: Routine Inspiratory Muscle Training within COPD Rehabilitation trial: #DRKS00004609; MCID study: #UMCG201500447.